196k views
1 vote
Jaleel and Lisa are simplifying the expression 2 (x minus 2) + 2 as shown. Jaleel's Method 2 (x minus 2) + 2 = 2 x minus 4 + 2 = 2 x minus 2 Lisa's Method 2 (x minus 2) + 2 = 2 x minus 2 + 2 = 2 x

User FlorisdG
by
5.8k points

2 Answers

4 votes

Answer:

d

Step-by-step explanation:

User MatanRubin
by
6.2k points
1 vote

Answer:

Jaleel is correct

Step-by-step explanation:

Given


2(x - 2) + 2

Jaleel


2(x - 2) + 2 = 2x - 4 + 2 = 2x - 2

Lisa


2(x - 2) + 2 = 2x - 2 + 2 = 2x

Required

Who is correct

Analyzing the solutions

For, Jaleel; we have:


2(x - 2) + 2 = 2x - 4 +2 --- this is correct


2(x - 2) + 2 = 2x - 2 --- this is correct

For Lisa, we have:


2(x - 2) + 2 = 2x - 2+2 --- this is incorrect because:


2(x - 2) + 2 \\e 2x - 2+2

Hence, Jaleel is correct

User Yogesh MV
by
5.2k points